Maydis stigma Improves Physical Traits and Unchanged Sensory Properties of Beef and Chicken Patties - Wan Rosli, W. I.; Nurhanan, A. R.; Solihah, M.A.; Mohsin, S. S. J. (World Academy of Science, Engineering and Technology (WASET), 2010)
The proximate composition, physical traits and sensory properties of beef and chicken patties incorporated with various level of dried cornsilk (Maydis stigma) were studied. The beef and chicken patties were formulated with either 2%, 4% or 6% of cornsilk. Both cooked beef and chicken patties incorporated with 6% cornsilk recorded the highest protein concentration at 23.3% and 28.42%, respectively. Both cooked beef and chicken patties containing 6% cornsilk significantly recorded the lowest concentration of fat at 11.4% and 14.60%, respectively. Beef and chicken patties formulated with 6% cornsilk recorded the highest cooking yield at 80.13% and 83.03% compared to other treatments. The inclusion of cornsilk did not change the sensory properties and consumer acceptability of cornsilk-based beef and chicken patties. Cornsilk fibre has been effective in improving cooking yield, moisture and fat retention of beef and chicken patties